Possibility for avoidance of urgent nighttime operations for acute appendicitis in a regional core university hospital. Issue 1 (18th May 2021) - Tago, Tomoya; Shimoda, Mitsugi; Imazato, Ryosuke; Udou, Ryutaro; Katsumata, Kenji; Tsuchida, Akihiko; Suzuki, Shuji
Abstract: Introduction: In recent years, a shortage of surgeons and anesthesiologists, particularly in regional hospitals, has become a social issue in Japan. In such hospitals, urgent surgery at night has been performed with difficulty. Therefore, we retrospectively assessed the outcomes of appendectomies for the patients visited at nighttime in our hospital categorized as a local university hospital. Methods: A retrospective review was conducted on 82 patients of acute appendicitis presented to our hospital between 5:30 p.m . to 8:30 a.m ., between January 2014 and April 2019. We compared patients who underwent urgent nighttime appendectomy (group A) and patients who underwent appendectomy during the daytime, or so‐called short interval appendectomy (group B). The evaluated factors were preoperative characteristics (age, sex, body mass index, cardiopulmonary complications, laboratory data, body temperature, presence of the Blumberg sign, and CT findings), operation characteristics, and postoperative characteristics (surgical‐site infection [SSI], complications, and length of hospital stay). Results: Patients in group A were significantly younger than patients in group B. Patients in group A were significant more likely to experience an SSI. Discussion: Patients diagnosed with acute appendicitis during the nighttime can undergo short interval appendectomy, which leads to a decreased risk of SSI, has no effect on length of hospital stay after surgery, and lessens medical staff burden.